Implementation of the Rapid Application Development (RAD) Method in the Development of Sales Applications at Coffee Shops Using the Apriori Algorithm: Case study: SIMERA Coffee Shop - Nanda Diaz Arizona; Yulia Yulia; Rabiatul Adwiya (Indonesian Scientific Journal, 2023)
Simera Coffee is a small and medium-sized business that focuses on selling typical Indonesian coffee products in the form of coffee powder, where each type of coffee is obtained from specific and trusted suppliers to maintain coffee quality and consumer confidence. The problem is that business people must be able to set patterns in knowing item items, maximize data utilization, and store expenditure data without being analyzed in detail; moreover, difficulties in restocking, so product expenditure data do not know the pattern of the data. Sales transaction data is continuously increasing every day, causing the need for ample data storage. The apriori algorithm can be applied to a sales data management application or cashier application, which has the function of recording coffee powder sales transactions and, at the same time, providing the function of analyzing sales data contained in the database using the a priori algorithm.